Efektivitas Peran Penyuluh Pertanian Dalam Budidaya Cengkih di Kabupaten Enrekang (Studi Kasus di Desa Buntu Barana Kecamatan Curio Kabupaten Enrekang) - Ida Rosada; Rasmeidah Rasyid; Nurliani; Farizah D. Amran; Sitti Nurani Sirajuddin; Nurhapsa; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2024)
Extension workers are among the contributors to agricultural activities. They are to provide guidance and knowledge through the latest information or innovation to enhance farming systems, which ultimately increases crop yields. Additionally, extension workers pursue to transform the behavior of farmers, for instance, their ability to adapt to continually changing situations and conditions. This research aims to analyze the role and effectiveness of agricultural extension in clove plantations in Enrekang Regency. The research was carried out in Buntu Barana Village, Curio District, Enrekang Regency, with 100 farmers as respondents. The results revealed that the extension process employing a group approach method attended by farmers and extension workers who provide knowledge regarding clove cultivation, starting from seeding, maintenance and fertilization, pest control, and postharvest, was successful, meeting farmers’ expectations. In this case, the instructor carries out his role well and effectively. The roles of agricultural instructors are facilitators, communicators, and motivators in the clove cultivation in Buntu Barana Village, Curio District, and they have been considered by the farmers effective in carrying out all roles, especially in clove cultivation activities.